Innovative Technical Guidance: Processing Corn Straw into Quality Feed for Beef Cattle for Veterinary Medicine Students at UNDIKMA with an Entrepreneurship Focus - Mashur Mashur (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
This study aims to improve the knowledge and skills of Veterinary Medicine students at UNDIKMA in processing corn straw into quality beef cattle feed through entrepreneurship-focused technical guidance. Our partners included local beef cattle farmers and student groups from the Faculty of Veterinary Medicine, UNDIKMA. We utilized a technology demonstration method showcasing four corn straw processing technologies: hay making, wet ammoniation, dry ammoniation, and haylage making. Results from pretest and posttest assessments of 41 students showed significant improvements in knowledge (average increase of 46.9%) and skills (average increase of 70.8%). Participants also demonstrated high willingness and readiness to apply and disseminate the techniques learned. We recommend the expansion of this training model to include more innovative processing methods and wider dissemination through various extension methods to effectively address the feed challenges in the beef cattle industry.